SAT0418 The Effect of Bisphosphonates on Bone Mineral Density in Patients with Ankylosing Spondylitis in Daily Clinical Practice. (15th July 2016) - Arends, S.; Veneberg, J.G.; Wink, F.R.; Bos, R.; Brouwer, E.; van der Veer, E.; Bootsma, H.; van Roon, E.N.; Maas, F.; Spoorenberg, A.
Abstract : Background: Ankylosing spondylitis (AS) is not only characterized by excessive bone formation, but also by excessive bone loss which may lead to low bone mineral density (BMD). So far, little is known about the effect of treatment with bisphosphonates on BMD in patients with AS. Objectives: To evaluate the effect of bisphosphonates in combination with calcium/vitamin D supplements on BMD over 2 years in patients with AS stratified for the use of TNF-α inhibitors. Methods: Patients from the Groningen Leeuwarden AS (GLAS) cohort, fulfilling the modified New York criteria for AS, who were treated with bisphosphonates and had 2-year follow-up BMD measurements available were included. All patients were treated with bisphosphonates in combination with calcium and/or vitamin D supplements. Alendronate (70 mg/week) and risedronate (35 mg/week) were used most frequently. BMD of the lumbar spine (anterior-posterior projection at L1-L4) and hip (total proximal femur) were measured using DXA. Wilcoxon-signed rank test was used to compare BMD scores at first visit and after 2 years. Analyses were stratified for the use of TNF-α inhibitors. Results: In total, 28 patients were included; 68% were male, 82% HLA-B27+, mean age was 53 ± 14 years, median symptom duration 20 years (range 1–60), and mean BASDAI 5.1±2.5. Fifteen patients (54%) started treatment with bisphosphonates before inclusion in the GLAS cohort (median 3.1 years). Most patients (86%) used bisphosphonates during the entire 2-year follow-up within GLAS. Overall, lumbar spine BMD increased significantly from median Z-score of -0.8 at first visit to -0.3 after 2 years of treatment with bisphosphonates within the GLAS cohort. Hip BMD increased significantly from -1.1 at first visit to -0.9 after 2 years. In the 10 patients not using TNF-α inhibitors, only lumbar spine BMD increased significantly after 2 years of treatment. In the 14 patients starting TNF-α inhibitors, lumbar spine and hip BMD increased significantly after 2 years. The remaining 4 patients already used TNF-α inhibitors (Table 1 ). Comparable results were found for BMD T-scores. Conclusions: In our observational cohort study, lumbar spine BMD improved significantly after 2 years of follow-up in all AS patients treated with bisphosphonates. This improvement was most pronounced in patients starting TNF-α inhibitors. Hip BMD only improved significantly in patients also starting TNF-α inhibitors. Acknowledgement: The GLAS cohort was supported by an unrestricted grant from Pfizer. Pfizer had no role in the design, conduct, interpretation, or publication of this study. Disclosure of Interest: S. Arends Grant/research support from: Pfizer, J. Veneberg: None declared, F. Wink Consultant for: Abbvie, R. Bos Grant/research support from: Pfizer, E. Brouwer Grant/research support from: Pfizer, E. van der Veer: None declared, H. Bootsma: None declared, E. van Roon: None declared, F. Maas: None declared, A. Spoorenberg Grant/research support from: Abbvie, Pfizer, UCB, Consultant for: Abbvie, Pfizer, MSD, UCB, Novartis